The Effect of Three Spacing and Goat Urine Application on Early Growth of Manglid - Aditya Hani (Jurnal Wasian, 2016)
The productivity of manglid (Magnolia champaca (L.) Baill. Ex Pierre) as the prominent plant commodity in West Java, can be improved by environmental manipulation such as spacing and fertilization. The objective of this research is to identify the effect of plant spacing and the use of goat urine as the leaves fertilizer on manglid planting until 19 month old. We used Randomized Block with Split Plot Design using three times replication. Main factor to be considered is the plant spacing with three different space :3  x 3 m (J1) ; 2  x 3 m (J2) and 2  x 2 m (J), while the secondary factor is three different doses of goat urine given : control (P1), 240 ml (P2), and 480  ml(P3. The results showed that the best treatment of planting manglid were treatment spacing of 2 x 2 m with goat urine fertilizer application as much as 240 ml per plant that produces high 191,5 cm and 3.83 cm of diameter up to the age of 19 months.